Senior High School English Teachers' Knowledge of Intercultural Values - Novia Astri Maulidya; Bambang Arya Wija Putra; Areta Puspa (EFL Education Journal, 2022)
The objective of this research was to know the level of senior high school English teachers’ knowledge of intercultural values. The study was concerned with the English teachers’ knowledge of intercultural value which is using a quantitative method, specifically, a survey study because it helped to describe the attitude, opinions, behaviors, or characteristics of the population. In this study, the participants included 66 in-service Senior High School English teachers from different public school around Jember from the total number 207 of senior high school English teachers in Jember. The participant selected was using random sampling by delivering the questionnaire to all of Senior High School English teachers in Jember. The data of this study used Cultural Intelligence Scale (CQS) which contains 20-item scales. The result of this study showed that among four dimensions of CQS, all of them got high level of senior high school English teachers’ knowledge of intercultural value which in this case very important for teachers to communicate across various culture